2005
DOI: 10.1213/01.ane.0000159150.79908.21
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Femoral Nerve Blockade in Conjunction with Epidural Analgesia After Total Knee Arthroplasty

Abstract: Either epidural analgesia or femoral nerve blockade improves analgesia and rehabilitation after total knee arthroplasty. No study has evaluated the combination of femoral nerve blockade and epidural analgesia. In this prospective, randomized, blinded study we investigated combining femoral nerve blockade with epidural analgesia. Forty-one patients received a single-injection femoral nerve block with 0.375% bupivacaine and 5 microg/mL epinephrine; 39 patients served as controls. All patients received combined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 11 publications
1
46
0
Order By: Relevance
“…All patients received intraoperative femoral nerve blocks with 30 mL bupivacaine 0.25% with epinephrine 1:200,000 for postoperative pain control as per institutional practice [22]. Patients were monitored according to American Society of Anesthesiologists guidelines [2].…”
Section: Methodsmentioning
confidence: 99%
“…All patients received intraoperative femoral nerve blocks with 30 mL bupivacaine 0.25% with epinephrine 1:200,000 for postoperative pain control as per institutional practice [22]. Patients were monitored according to American Society of Anesthesiologists guidelines [2].…”
Section: Methodsmentioning
confidence: 99%
“…However, of those studies, only nine of 21 (43%) explicitly reported blinding of patients, clinicians, and/or assessors to the participants' treatment arm allocation [4,12,15,20,24,27,29,47,48]. Only nine of 21 (43%) reported performing an a priori power calculation for the outcome of postoperative cognitive dysfunction [4,16,24,27,29,34,38,39,48], with one of these studies failing to recruit a sufficient number of patients [38]. Of the remaining seven studies, two used a prospective comparative design [2,41], two used a case-control design [33,44], and three used a retrospective comparative design [17,19,36].…”
Section: Study Designs and Populationsmentioning
confidence: 99%
“…This included eight studies of patients who underwent either TKA or THA [7,12,17,18,20,24,36,47], eight studies of patients who underwent unilateral TKA [15,19,26,35,39,41,45,48], two studies of patients who underwent unilateral THA [16,34], and one study of patients who underwent bilateral TKA [46]. The remaining nine studies encompassing 2426 patients investigated postoperative cognitive dysfunction in a mixed major noncardiac surgical population, which included patients who underwent elective joint arthroplasty.…”
Section: Study Designs and Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common indications include knee arthroplasty, arthroscopy, ligament reconstruction, foot and ankle surgery, and management of femoral fractures. [4][5][6] The use of a FNB together with general anaesthesia reduces the required doses of general anaesthetic agents, and hence its side-effects, including nausea, vomiting, drowsiness, and respiratory depression. The FNB also confers superior pain control, decreases opioid requirement, and enables earlier ambulation and hospital discharge.…”
Section: Introductionmentioning
confidence: 99%